Modern database management - Hoffer, Jeffrey A (Pearson/ Prentice Hall, 2005)
This book has been updated and revised to accommodate the technical, managerial, and methodological changes occurring at an ever-increasing pace in this field. While retaining the best features of the previous edition, it covers the latest principles, concepts, and technologies. Illustrations help make important concepts and techniques clear. It includes object-oriented data modeling and UML, Internet databases, data warehousing, and the use of CASE tools in support of data modeling. Topics are introduced to reinforce principles from other typical information fields, such as systems analysis and design, networking, Website design and development, MIS principles, and computer programming. Emphasis is on the development of the database component of modern information systems, and on the management of the data resource. For managers of information systems, as well as systems analysts and database designers